2013
DOI: 10.2109/jcersj2.121.981
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Al doped zinc oxide films prepared by electron beam-PVD

Abstract: Al doped ZnO (AZO) films were prepared on quartz substrates by the co-evaporation of ZnO and Al 2 O 3 by EB-PVD. Structural, optical and electrical properties of AZO films were investigated, focusing on the effect of the electron beam power applied to the Al 2 O 3 ingot. X-ray diffraction measurement showed that the AZO films were highly c-axis oriented. Transmittance of all the AZO films was over 85% in the visible range. The highest reflectance in the near IR range was obtained at the EB power on Al 2 O 3 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…Paper [99] discusses the results of coating deposition of zirconium-and alumina-based ceramics by a high-power electron beam (Figure 11). The coatings were produced by scanning an electron beam over two evaporated targets: a conductive target of ZnO and a dielectric target of Al2O3.…”
Section: Electron-beam Methodsmentioning
confidence: 99%
“…Paper [99] discusses the results of coating deposition of zirconium-and alumina-based ceramics by a high-power electron beam (Figure 11). The coatings were produced by scanning an electron beam over two evaporated targets: a conductive target of ZnO and a dielectric target of Al2O3.…”
Section: Electron-beam Methodsmentioning
confidence: 99%
“…Okuhara et al1) showed sputtering at 200°C and X-ray diffraction indicated (002) and (004) peaks. Yamaguchi et al 18) also heated the substrate at 400°C and observed clear (002) and (004) peaks. Figure 7 shows a photograph of thin film deposited in the shield.…”
Section: Jcs-japanmentioning
confidence: 98%